Occurrence of Fusarium species in maize kernels grown in northwestern Spain. (25th November 2013) - Aguín, O.; Cao, A.; Pintos, C.; Santiago, R.; Mansilla, P.; Butrón, A.
<x xml:space="preserve">Abstract</x> Fusarium poses food and feed safety problems because most species produce mycotoxins. To understand the epidemiology of the Fusarium disease, efforts must focus more precisely on how environmental variables affect disease presence. The objectives of the present study were to monitor the occurrence of Fusarium species in maize kernels in northwestern Spain to determine the risk of mycotoxin contamination and to identify environmental traits affecting the composition of the Fusarium species identified. A combination of 24 environments was evaluated. The percentage of kernels infected by F. verticillioides ranged from 33 to 99%, supporting the idea that fumonisin contamination is the main maize‐based feed and food safety concern in this area. In this region, temperature and humidity primarily affected Fusarium spp. occurrence. Warmer temperatures during the later stages of kernel development and during kernel drying increased the frequency of F. verticillioides in maize kernels, while the presence of F. subglutinans was increased by higher relative humidity during the silking stage and cooler temperatures during kernel drying.